FARAID AND HIBAH AS ISLAMIC ESTATE PLANNING TOOLS AMONG MUSLIM SOCIETY IN MALAYSIA, THE CONCEPT, IMPORTANCE AND ISSUES (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
If the rise in the Muslim population is not counterbalanced by a greater awareness and understanding of Islamic inheritance laws, including the process and procedure used in Malaysia to manage the property, the increase in unclaimed inheritance estate, which has reached more than RM 70 billion, will become more critical. In fact, because the heirs are unfamiliar with the property distribution procedure, they have chosen to ignore the current alternatives. Consequently, it may result in issues such as conflicting claims, undeveloped land, complexity of the trial procedure, and the possibility of losing the deceased's documents. Thus, this research aims to highlight the concept including the law governing and its procedure, significance, and related issue of faraid and hibah as Islamic estate planning tools among Muslim society in Malaysia as a mean of resolving inheritance distribution difficulties. Besides, this article applies a qualitative study by scrutinizing the literature descriptively including article journals from several online databases and semi structured interviews with the experts that involves related open-ended and probing questions for the purpose of finding the best and suitable tools of Islamic estate planning for the society according to their needs. Therefore, it is hoped that this article will be able to contribute to an effort of encouraging the Muslim’s society in planning and managing their estate properly.